Aplicação de solventes eutéticos profundos hidrofóbicos na determinação de parabenos e bisfenol A em amostras de lodo de esgoto usando cromatografia gasosa acoplada à espectrometria de massas com introdução da amostra via pirolisador - Ferreira, Karen Chibana [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The presence of emerging contaminants (ECs) has been the subject of discussions due to concerns about the risks these compounds pose to human health and the environment. In this context, the pursuit of environmentally sustainable analytical methods has been considered essential. One response to this demand has been the recent generation of solvents, including hydrophobic deep eutectic solvents (HDES), which have been prepared by combining two or three precursors, establishing intermolecular hydrogen bonds between a donor species (HBD) and an acceptor species (HBA). Thus, the main objective of the study was to contribute to the advancement of sustainable analytical methods, providing an efficient approach for the detection and quantification of ECs in environmental samples, such as sludge, using HDES as extracting solvents. The characterization of these solvents involved the evaluation of parameters such as density and viscosity, as well as the use of Fourier-transform infrared spectroscopy (FTIR). The preparation of HDES from precursors such as DL-menthol (HBA) and organic acids (decanoic, dodecanoic, acetic), acting as HBDs, was quick and simple, involving heating the mixture at 60°C for 20 minutes followed by cooling to room temperature. All HDES were clear, except for dodecanoic acid, which exhibited a yellowish color due to the precursor used. Despite having a density lower than water, facilitating the collection of the organic phase for analysis, HDES had higher viscosity compared to water. Characterization by FTIR and thermoanalytical analyses confirmed the formation of the solvent, evidenced by the presence of the hydroxyl (O─H) absorption band and endothermic events indicating lower melting points of HDES compared to their pure precursors. Factorial design analyzed temperature, time, and sample volume for application in the determination of methylparaben (MeP), propylparaben (PrP), butylparaben (BuP), and bisphenol A (BPA). Chemometric tools indicated that the analytical response was directly proportional to the increase in injection volume, with the ideal value being 20 μL. In dispersive liquid-liquid microextraction (DLLME), the optimal conditions were 300 μL of HDES, 350 μL of ACN as a dispersing solvent, pH equal to 10, sludge dilution by 50 times, and 27% m/v of NaCl. Evaluation of the figures of merit indicated a recovery rate exceeding 90%, intra- and inter-day precisions below 15%, and the limit of detection (LOD) established in the range of 25 to 50 μg L-1. The method demonstrated selectivity, avoiding interferents in the analytical response. The application of HDES in environmental matrices allowed the determination of emerging contaminants, following the principles of sustainable analytical chemistry, which was confirmed by applying the AGREE evaluation metric system, resulting in values of 0.72 and 0.76 corresponding to the method used and sample preparation.

A presença de contaminantes emergentes (CEs) foi o foco de discussões, devido à preocupação com os riscos que esses compostos representavam para a saúde humana e ao meio ambiente. Nesse contexto, a busca por métodos analíticos ambientalmente sustentáveis era considerada essencial. Uma resposta a essa demanda foi a geração recente de solventes, incluindo os solventes eutéticos profundos hidrofóbicos (HDES), que foram preparados pela combinação de dois ou três precursores, estabelecendo ligações de hidrogênio intermoleculares entre uma espécie doadora (HBD) e uma espécie receptora (HBA). Deste modo, o objetivo principal do estudo desenvolvido foi contribuir para o avanço de métodos analíticos sustentáveis, fornecendo uma abordagem eficiente para a detecção e quantificação de CEs em amostras ambientais, como lodo, utilizando os HDES como solventes extratores. A caracterização desses solventes envolveu a avaliação de parâmetros como densidade e viscosidade, além do uso da espectroscopia no infravermelho por transformada de Fourier (FTIR). A preparação dos HDES a partir de precursores como o DL-mentol (HBA) e ácidos orgânicos (decanóico, dodecanóico, acético), atuando como HBDs, foi rápida e simples, com aquecimento da mistura a 60 ºC por 20 minutos, seguido de resfriamento à temperatura ambiente. Todos os HDES eram límpidos, com exceção do ácido dodecanóico, que apresentava coloração amarelada devido ao precursor usado. Apesar de terem densidade menor que a água, facilitando a coleta da fase orgânica para análises, os HDES possuíam viscosidade maior em comparação com a água. A caracterização por FTIR e análises termoanalíticas confirmaram a formação do solvente, evidenciada pela presença da banda de absorção referente à hidroxila (O─H) e eventos endotérmicos indicando pontos de fusão inferiores dos DES em comparação com seus precursores puros. O planejamento fatorial analisou temperatura, tempo e volume de amostra para aplicação na determinação de metilparabeno (MeP), propilparabeno (PrP), butilparabeno (BuP) e bisfenol A (BPA). Ferramentas quimiométricas indicaram que a resposta analítica era diretamente proporcional ao aumento do volume de injeção, sendo o valor ideal de 20 μL. Na microextração líquido-líquido dispersiva (DLLME), as condições ótimas foram 300 μL de HDES, 350 μL de ACN como solvente dispersor, pH igual a 10, diluição do lodo em 50 vezes e 27% m/v de NaCl. A avaliação das figuras de mérito indicou recuperação superior a 90 %, precisões intra e inter dia inferiores a 15 %, e o limite de detecção (LOD) foi estabelecido em um intervalo de 25 a 50 μg L-1. O método demonstrou seletividade, evitando interferentes na resposta analítica. A aplicação dos HDES em matrizes ambientais permitiu a determinação de contaminantes emergentes, seguindo os princípios da química analítica sustentável, o que foi confirmado aplicando o sistema métrico de avaliação AGREE, no qual apresentou valores de 0,72 e 0,76 correspondentes ao método utilizado e o preparo de amostra.
Application of hydrophobic deep eutectic solvents in the determination of parabens and bisphenol A in sewage sludge samples using gas chromatography coupled with mass spectrometry with sample introduction via pyrolyzer
Keywords: Preparo de amostras; Misturas; Pirólise; Cromatografia a gás; Contaminantes emergentes; Sample preparation; Mixtures; Pyrolysis; Gas chromatography; Emerging contaminants